PENENTUAN HARGA POKOK PRODUKSI JAMUR DENGAN METODE FULL COSTING PADA CELEBES MUSHROOM FARM - Mashud Mashud; Askar Askar; Yuliana Yuliana (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2020)
Companies in determining the selling price must calculate the cost of production accurately. Celebes Mushroom Farm in calculating the cost of production is done by counting manually. This research was conducted to make an application that can provide information about the overall costs incurred by Celebes Mushroom Farm in producing mushrooms. The cost calculation used the Full Costing method with Delphi 7.0 as the programming language and MySQ used in the database. Data collection by interviewing and observing techniques at Celebes Mushroom Farm and by library research. From the results of the design of the application of the cost of production, can record and calculate the cost of raw materials, labor, and fixed and variable factory overhead by computerized. And the implementation of the calculation of the cost of production using the full costing method shows that this application can calculate the cost of production accurately.